Rapid Independent Health Literacy Assessment: A Pilot Study Among Native English-speaking and Low English Proficiency Patients - John Blade Hargiss; Jeffery D. St. Jeor; Jennifer L. Horn; Gregory M. Garrison (SAGE Publishing, 2021)
Objectives: Health literacy is an individual's capacity to obtain, process, and understand basic health information needed to make appropriate health decisions. Failure to understand and correctly execute a plan of care often leads to poor health outcomes. Determining patient health literacy allows health care providers to tailor their plan of care instructions, increasing the probability of understanding, and adherence. Several validated health literacy tests have been developed to assess the health literacy of individuals and ethnic groups. However, because a proctor is required to administer these tests, their usefulness in clinical settings is limited. The issue of health literacy is especially relevant within minority groups. This research focused on producing a translatable assessment that can be administered quickly without a proctor. Methods: We developed a 15-question instrument (the RIHLA) in English using the Delphi method with a panel of bilingual experts and translated it into Spanish. Internal reliability was assessed using Cronbach's alpha for 3 groups: Native English-speaking College students (NESC), Native English-speaking patients (NES), and Limited English Proficient Spanish-speaking patients (LEP). External validity was assessed using Pearson's correlation coefficient to compare our instrument to a previously validated, proctored instrument measuring health literacy (the SAHL-E). Results: Four hundred fifteen subjects completed the RIHLA. Of these, 192 (46.3%) were NESC, 208 (50.1%) were NES, and 15 (3.6%) were LEP. The mean number of correct answers was 11.2, 11.6, and 8.3 respectively with the LEP group scoring lower ( P  < .01). Cronbach's alpha was >.70 for each group. Moderate correlation between the RIHLA and the previously validated instrument was present ( P  < .01) with Pearson's r  = .47 (95% CI: 0.18-0.69). Conclusion: The RIHLA is a non-proctored assessment tool that may provide a measure of patients' health literacy in multiple languages. Further studies with larger sample sizes are necessary to confirm the reliability, validity, and generalizability to a wider population.